The perceptions about xenophobia of a group of residents in Mukhomi village, Limpopo Province - Tshabalala, Ntwanano Patrick (Acta criminologica, 2018)
The focus of this article is on xenophobic attacks that erupted in South Africa, particularly in 2008 and 2015, which primarily targeted foreigners. The research was conducted through interviews in a rural community of Malamulele area called Mukhomi village in the Limpopo Province in South Africa. The village was selected for the study, particularly due to the poverty in the area and the influx of migrants. Respondents were probed on aspects of migration, employment and business opportunities and attitudes towards migrants. It is evident that economic hardships and competition for resources play an essential role in the attitudes that participants have towards migrants. Locals blame foreigners for taking job opportunities from them and unfair economic competition that leads to resentment. The article is based on interviews conducted with 35 villagers and highlights precipitating factors such as competition for resources, perceptions about the alleged crime committed by foreigners and land issues.